Easy Trigo.

Geometry Level 2

If sin θ + sin 2 θ = 1 \sin\theta+\sin^2\theta=1 Then find the value of, cos 12 θ + 3 cos 10 θ + 3 cos 8 θ + cos 6 θ 1 \cos^{12}\theta+3\cos^{10}\theta+3\cos^8\theta+\cos^6\theta-1


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Sanjeet Raria
Sep 11, 2014

Given sin θ = 1 sin 2 θ = cos 2 θ \sin\theta=1-\sin^2\theta=\cos^2\theta L.H.S cos 6 θ ( cos 2 θ + 1 ) 3 1 \cos^6\theta(\cos^2\theta+1)^3-1 = sin 3 θ ( sin θ + 1 ) 3 1 =\sin^3\theta(\sin\theta+1)^3-1 = ( sin θ ( sin θ + 1 ) ) 3 1 =(\sin\theta(\sin\theta+1))^3-1 = ( sin 2 θ + sin θ ) 3 1 = 1 3 1 = 0 =(\sin^2\theta+\sin\theta)^3-1=1^3-1=\boxed0

didnt get 3rd step of lhs

Amey Khairnar - 6 years, 8 months ago

Log in to reply

same with me

zMoh w - 6 years, 8 months ago

Hope that helped @Amey Khairnar @zMoh w

Sanjeet Raria - 6 years, 8 months ago

he took cube common

Siddhesh Patel - 6 years, 8 months ago

very good at factoring dude

Marcielow Callelero - 6 years, 8 months ago

This one is easy.

Les Narvasa - 6 years, 8 months ago

It's direct. When you see. two coefficients as 3, check : (a+b)^3. You get (cos^2 theta +cos^4 theta) ^3 - 1 . i.e. sin theta + sin^2 theta - 1 = cipher

Sankalp Ranjan - 6 years, 8 months ago

yes absolutely right answer.

Sandeep Kumar - 6 years, 7 months ago
Soumo Mukherjee
Oct 13, 2014

S i n c e v a l u e i s g i v e n i n t e r m s o f s i n θ I t h o u g h t i t m i g h t b e b e n e f i c i a l t o c o n v e r t t e r m s o f c o s θ i n s i n θ m o r e o v e r i t s a p p a r e n t t h a t i t c a n b e d o n e e a s i l y . A f t e r s u b s t i t u i t i n g ( cos 2 θ = sin θ ) I g o t t h e s e t e r m s : sin 3 θ + sin 6 θ + 3 sin 4 θ + 3 sin 5 θ 1 W h i c h o n r e a r r a n g i n g g a v e t h e s e : sin 3 θ + sin 6 θ + 3 sin 3 θ ( sin 2 θ + sin θ ) 1 I f i n a l l y s h o t t h e p r o b l e m b y t h i s : ( sin θ + sin 2 θ ) 3 1 = 0.. Since\quad value\quad is\quad given\quad in\quad terms\quad of\quad sin\theta \quad I\quad thought\\ it\quad might\quad be\quad beneficial\quad to\quad convert\quad terms\quad of\quad cos\theta \quad in\quad sin\theta \\ moreover\quad its\quad apparent\quad that\quad it\quad can\quad be\quad done\quad easily.\quad \\ After\quad substituiting(\cos ^{ 2 }{ \theta } =\sin { \theta } )\quad I\quad got\quad these\quad terms:\\ \\ \sin ^{ 3 }{ \theta } +\sin ^{ 6 }{ \theta } +3\sin ^{ 4 }{ \theta } +3\sin ^{ 5 }{ \theta } -1\\ \\ Which\quad on\quad rearranging\quad gave\quad these:\\ \\ \Rightarrow \sin ^{ 3 }{ \theta } +\sin ^{ 6 }{ \theta } +3\sin ^{ 3 }{ \theta } (\sin ^{ 2 }{ \theta } +\sin { \theta } )-1\\ \\ I\quad finally\quad shot\quad the\quad problem\quad by\quad this:\\ \Rightarrow { (\sin { \theta } +\sin ^{ 2 }{ \theta } ) }^{ 3 }-1=0..

Aloysius Ng
Oct 21, 2014

I didn't factorize all the way...

I took sin( θ \theta ) as X. X+ X 2 X^2 =1. After using the quadratic solver, X = [-1 ± \pm 5 \sqrt5 ]/2.

Also, sin( θ \theta )+[sin( θ \theta )]^2= cos( θ \theta )+[sin( θ \theta )]^2. sin( θ \theta )+[cos( θ \theta )]^2

The value becomes X^6+3X^5+3X^4+X^3-1=X^3(X+1)^3-1= {[-1 ± \pm 5 \sqrt5 ]/2}^3+{[1 ± \pm 5 \sqrt5 ]/2}^3-1

After some tiring calculations, I got 1-1=0. Argh... If I had realised...

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...